Experienced versus Inexperienced EFL Teachers` Beliefs of Self-Efficacy: The Case of Public and Private Sectors - Alijanian, Ehsan (Mediterranean Journal of Social Sciences, 2012)
Teacher self-efficacy is the confidence in one`s ability to motivate and promote positive outcomes in students. It can beinfluenced by contextual and demographic factors. The present study is an attempt to analyze the role of factors such as teachers`working environment, experience, and gender on teachers` beliefs about self-efficacy. For this purpose, 40 Iranian English as ForeignLanguage teachers (20 form public setting, and 20 from private setting) with different gender and work experience were chosen. Ateacher self efficacy scale and three open-ended questions were used to investigate the possible differences of teachers` beliefs withrespect to the variables mentioned. The results indicated that working environment, experience, and gender can effect teachers` beliefsof self-efficacy significantly. The findings have pedagogical implications for teacher education programs.